2020
DOI: 10.3389/fmicb.2020.01011
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Microbial Communities and Their Potential Role as Environmental Pollution Indicators in Xuande Atoll, South China Sea

Abstract: In this study, 39 sediment samples were collected from Qilian Island, Iltis Bank, and Yongxing Island in Xuande Atoll in the South China Sea (SCS), and the microbial community structures and distribution were analyzed. The microbial community was influenced by both natural environmental factors and human activities. The abundance of genera Vibrio and Pseudoalteromonas, which are associated with pathogenicity and pollutant degradation, were significantly higher in Qilian Island than in Yongxing Island and Iltis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Atolls represent isolated island biomes, which are rarely investigated often due to their remoteness. Studies on microbes have been undertaken i.e., at the Line Islands 14 , including the largest atoll Kiritimati 15 , 16 , or at Xuande Atoll 17 . They focus on microbial communities in microbial mats 16 , the water column 18 and associated coral reefs 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atolls represent isolated island biomes, which are rarely investigated often due to their remoteness. Studies on microbes have been undertaken i.e., at the Line Islands 14 , including the largest atoll Kiritimati 15 , 16 , or at Xuande Atoll 17 . They focus on microbial communities in microbial mats 16 , the water column 18 and associated coral reefs 14 .…”
Section: Introductionmentioning
confidence: 99%
“…They focus on microbial communities in microbial mats 16 , the water column 18 and associated coral reefs 14 . Sediments are only covered regarding the uppermost 5–10 cm of depth 15 , 17 , and mostly provide only limited (or no) information on the sedimentary facies and porewaters. Geochemical gradients and bacterial community composition in tropical atoll sediments reaching below 10 cm of depth have, to our knowledge, not been assessed to date.…”
Section: Introductionmentioning
confidence: 99%
“…Reconstruction of microbial networks can advance our knowledge of the complex behaviours in microbial communities and predict the effects of perturbations on community dynamics (Röttjers & Faust, 2018). Previous studies have used network analysis to explore interactions between marine benthic microbes and microbe–environment relationships (Buongiorno et al, 2019; Wang et al, 2020; Zhang, Li, et al, 2020), but most of these studies focused only on shallow sediments and none of them revealed the vertical shift of microbial networks in the subseafloor. In addition, network analysis can be a powerful tool for inferring the keystone taxa in a microbial community which can drive community composition and function irrespective of their abundance (Banerjee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In these sedimentary environments, anaerobic conditions prevail due to lack of oxygen exposure. The homo-acetogenic and other microbial populations are largely determined by abiotic conditions of these environments, such as the location, depth, acidity, temperature, and sediment compositions [50,51]. Anoxic conditions favor the generation of a number of electron donors by virtue of hydrolysis and fermentation reactions [52].…”
Section: Sedimentary Environmentsmentioning
confidence: 99%